Religion, toleration, and British writing, 1790-1830 - Canuel, Mark (Cambridge studies in Romanticism ;, 2002)
Canuel examines the way that Romantic poets, novelists and political writers criticised the traditional grounding of British political unity in religious conformity. Canuel shows how Romantic writers including Bentham, Radcliffe, Edgeworth and Byron saw their works as political and literary commentaries on the extent and limits of religious toleration.